Cytotoxicity Analysis of Nineteen Medicinal Plants Extracts on Breast Adenocarcinoma (MCF-7) and Rhabdomyosarcoma (RD) Cancer Cell Lines - Yemi Adekunle; Babatunde Samuel; Toluwanimi Emmanuel; Johnson Adeniji; Omonike Ogbole (Shiraz University of Medical Sciences, 2022)
The burden of cancer is alarmingly great on humans. However, the relevance of plants in combating cancer cannot be undermine. We joined the global search for anticancer agents from plants by screening nineteen (19) medicinal plant extracts on human breast carcinoma (MCF-7) and rhabdomyosarcoma (RD) cell lines using the 3- [4, 5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay. Vincristine was used as the positive reference. Results were presented as mean IC50±standard error of the mean using GraphPad Prism (6.0). One-way ANOVA was used to establish the level of statistical significance. The results showed that twelve of the extracts were moderately cytotoxic on MCF-7 while seven were moderately active on RD (IC50, 30-100 µg/mL). Two of the extracts, Afzelia africana stem and Anogeissus leiocarpus root, showed significant activity on MCF-7 while seven had significant activity on RD (IC50   Please cite this article as: Yemi A. Adekunle, Babatunde B. Samuel*, Toluwanimi E Akinleye, Adekunle J. Adeniji, Omonike O. Ogbole. Cytotoxicity Analysis of Nineteen Medicinal Plants Extracts on Breast Adenocarcinoma (MCF-7) and Rhabdomyosarcoma (RD) Cancer Cell Lines. Trends in Pharmaceutical Sciences. 2022;8(1):57-64 .doi: 10.30476/TIPS.2022.94313.1136